Pakistan : Eleventh Review Under the Extended Arrangement and Request for Modification of Performance Criteria and Extension of the Extended Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report, 2016)
This paper assesses El Salvador's capacity and options for upgrading its fiscal framework and attempts to take a fresh look at the 'growth puzzle' from a comparative perspective. The Hausmann's growth diagnostics approach offers a useful start, but it does not clearly explain El Salvador's growth gap versus its regional peers. The paper also constructs estimates of potential output growth and the output gap for El Salvador and compares it to those of other Central American countries. It examines potential growth before and after the global financial crisis and its likely medium-term trajectory.